Visualizing posthuman conservation in the age of the Anthropocene - Propen, Amy D. (New directions in rhetoric and materiality., 2018)
"Merges a visual-material rhetorical framework with ideas about environmental conservation and the posthuman to examine cases in which visual technologies play a prominent role in arguments to protect threatened marine species: photographs of ocean plastics, seismic testing debates, and conservation maps created from GPS tracking. Advances a notion of posthuman environmental conservation"--